KONSEP KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS FIQIH MINORITAS (STUDI KASUS MADRASAH TSANAWIYAH AL-IMAM CIKEMBAR KABUPATEN SUKABUMI) - Rahma, Farida Nur; Hidayat, Tatang; Kusumah, Mada Wijaya; Ibdalsyah, Ibdalsyah; Istianah, Istianah (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
This research aims to formulate a curriculum concept for Islamic Religious Education based on minority fiqh at the Madrasah Tsanawiyah (MTs) level. The subjects of this research are Madrasah Tsanawiyah Al-Imam Cikembar in Sukabumi Regency. This research is categorized as a qualitative approach using a case study method. Data were obtained through interviews, observations, and documentation. The study found that the concept of the Islamic Religious Education curriculum for minority Muslims is directed towards building harmonious relationships with followers of other religions. The teaching strategy emphasizes the Contextual Teaching and Learning (CTL) method, making students more responsive to the reality of diversity. The evaluation focuses on assessing the understanding and affective aspects of positive behavior within the plurality of society.